Affective neuroscience of pleasure: reward in humans and animals. - Berridge, K; Kringelbach, M (2008)
INTRODUCTION: Pleasure and reward are generated by brain circuits that are largely shared between humans and other animals. DISCUSSION: Here, we survey some fundamental topics regarding pleasure mechanisms and explicitly compare humans and animals. CONCLUSION: Topics surveyed include liking, wanting, and learning components of reward; brain coding versus brain causing of reward; subjective pleasure versus objective hedonic reactions; roles of orbitofrontal cortex and related cortex regions; subcortical hedonic hotspots for pleasure generation; reappraisals of dopamine and pleasure-electrode controversies; and the relation of pleasure to happiness.